PROLONGED EFFECT OF PRONE LUMBAR TRACTION AND PRONE LUMBAR TRACTION WITH SHORT WAVE DIATHERMY ON INDIVIDUAL HEIGHT A COMPARATIVE STUDY - AYYAPPAN JAYAVEL,; PROF. V.P.R. SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Traction has therapeutic effects over bones, ligaments, nerves, joints, intervertebral discs and muscles. Shortwave diathermy is proven to produce muscle relaxation, decrease muscle spasm and joint stiffness by increasing the collagen tissue extensibility and decrease tissue viscosity and tension. 50 normal college males were selected by the simple random sampling method. Initially the subjects receive prone lumbar traction. After 1 week the same subjects received shortwave diathermy and prone lumbar traction. The post test height was measured immediately and subsequently every 10 minutes for 60 minutes. Stadiometer was used to measure the height in millimeters. The prolonged effect of traction was found to be for 20 minutes and after that it gradually decreased. The prolonged effect of shortwave diathermy and traction remained for 30 minutes and then started reducing gradually. This study showed the effect of prone lumbar traction can be prolonged by applying shortwave diathermy before traction.